Autophagy complements metalloprotease FtsH6 in degrading plastid heat shock protein HSP21 during heat stress recovery. (29th June 2021) - Sedaghatmehr, Mastoureh; Thirumalaikumar, Venkatesh P; Kamranfar, Iman; Schulz, Karina; Mueller-Roeber, Bernd; Sampathkumar, Arun; Balazadeh, Salma
Abstract : Plastidic heat shock protein HSP21 is a key positive element of heat stress memory in Arabidopsis. We demonstrate that autophagy controls HSP21 abundance during memory, jointly with metalloproteases. Abstract: Moderate and temporary heat stresses prime plants to tolerate, and survive, a subsequent severe heat stress. Such acquired thermotolerance can be maintained for several days under normal growth conditions, and can create a heat stress memory. We recently demonstrated that plastid-localized small heat shock protein 21 (HSP21) is a key component of heat stress memory in Arabidopsis thaliana . A sustained high abundance of HSP21 during the heat stress recovery phase extends heat stress memory. The level of HSP21 is negatively controlled by plastid-localized metalloprotease FtsH6 during heat stress recovery. Here, we demonstrate that autophagy, a cellular recycling mechanism, exerts additional control over HSP21 degradation. Genetic and chemical disruption of both metalloprotease activity and autophagy trigger superior HSP21 accumulation, thereby improving memory. Furthermore, we provide evidence that autophagy cargo receptor ATG8-INTERACTING PROTEIN1 (ATI1) is associated with heat stress memory. ATI1 bodies co-localize with both autophagosomes and HSP21, and their abundance and transport to the vacuole increase during heat stress recovery. Together, our results provide new insights into the module for control of the regulation of heat stress memory, in which two distinct protein degradation pathways act in concert to degrade HSP21, thereby enabling cells to recover from the heat stress effect at the cost of reducing the heat stress memory.